2006
DOI: 10.1186/1471-2407-6-178
|View full text |Cite
|
Sign up to set email alerts
|

Trends in incidence and mortality of nasopharyngeal carcinoma over a 20–25 year period (1978/1983–2002) in Sihui and Cangwu counties in southern China

Abstract: Background: Nasopharyngeal carcinoma (NPC) is a rare malignancy in most parts of the world but is common in southern China. A recent report from the Hong Kong Cancer Registry, a high-risk area for NPC in southern China, showed that incidence rate decreased by 29% for males and by 30% for females from 1980-1999, while mortality rate decreased by 43% for males and 50% for females. Changing environmental risk factors and improvements in diagnosis and treatment were speculated to be the major factors contributing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
178
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 205 publications
(188 citation statements)
references
References 21 publications
10
178
0
Order By: Relevance
“…Although many other studies have found an inverse association between dietary (17)(18)(19)(20)(21)(22)(23) or blood (24)(25)(26)(27) folate and the risk for head and neck cancer, the numbers of NPC cases in these studies were generally <100. In addition, all of these studies were conducted among populations with dietary habits and NPC risks different from those of the Chinese in south China (1)(2)(3) . Thus, further study of the folate-NPC association in high-risk Chinese adults is necessary.…”
mentioning
confidence: 99%
“…Although many other studies have found an inverse association between dietary (17)(18)(19)(20)(21)(22)(23) or blood (24)(25)(26)(27) folate and the risk for head and neck cancer, the numbers of NPC cases in these studies were generally <100. In addition, all of these studies were conducted among populations with dietary habits and NPC risks different from those of the Chinese in south China (1)(2)(3) . Thus, further study of the folate-NPC association in high-risk Chinese adults is necessary.…”
mentioning
confidence: 99%
“…This trend differs from those of other regions in mainland China; the incidence rates of NPC in Shanghai (Yang et al, 2009), Wuhan (Xie et al, 2012a), Zhongshan (Wei et al, 2010), Sihui and Cangwu (Jia et al, 2006) were stable over a long period. However, the encouraging reduction seen in this study was similar to those observed in other developed regions with high NPC occurrence rates (Lee et al, 2003;Hsu et al, 2006;Luo et al, 2007;Arnold et al, 2013).…”
Section: Discussionmentioning
confidence: 76%
“…From 1973 to 2005, there was also a general trend of decrease in NPC mortality in both men and women in China (Huang et al, 2012). However, a similar study conducted over a 20-year period (1978-2002) in Sihui and Cangwu (Sihui county is located in the middle east part of Guangdong province, and Cangwu county is located in Guangxi province at the border between Guangxi and Guangdong) found stable incidence rates (Jia et al, 2006). Stable rates were also found in Zhongshan during 1970(Wei et al, 2010.…”
Section: Introductionmentioning
confidence: 93%
“…For example, in the Cantonese population, the peak incidence rate of NPC was 20 to 30 cases per 100,000. In the last few decades, incidence and mortality of NPC among Chinese in some areas of China and Asia have gradually declined (44,45). China will have an estimated 36,080 new cases and 22,558 deaths of NPC in 2015 (46).…”
Section: Field and Laboratory Studies On Nasopharyngeal Carcinomamentioning
confidence: 99%